2020
DOI: 10.1113/ep088265
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caffeine on neuromuscular function in a non‐fatigued state and during fatiguing exercise

Abstract: Caffeine enhances exercise performance, but its mechanisms of action remain unclear. In this study, we investigated its effects on neuromuscular function in a non-fatigued state and during fatiguing exercise. Eighteen men participated in this randomized, double-blind, placebo-controlled crossover trial. Baseline measures included plantarflexion force, drop jump, squat jump, voluntary activation of triceps surae muscle, soleus muscle contractile properties, M-wave, -motoneuron excitability (H-reflex), corticosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 85 publications
0
19
0
Order By: Relevance
“…Acute caffeine intake has no reported effect on SAI and LAI [ 158 ], or SICI [ 154 , 157 , 158 ]. One study reported a reduction in SICI following caffeine intake, although a similar finding was also observed in the placebo condition [ 155 ]. This suggests that the change in SICI was not due exclusively to the effects of caffeine.…”
Section: Caffeinementioning
confidence: 71%
See 4 more Smart Citations
“…Acute caffeine intake has no reported effect on SAI and LAI [ 158 ], or SICI [ 154 , 157 , 158 ]. One study reported a reduction in SICI following caffeine intake, although a similar finding was also observed in the placebo condition [ 155 ]. This suggests that the change in SICI was not due exclusively to the effects of caffeine.…”
Section: Caffeinementioning
confidence: 71%
“…First, acute caffeine intake has no effect on threshold [ 154 , 155 , 156 , 157 , 158 ]. Multiple studies have reported no change in resting MEPs following caffeine intake, at intensities ranging from 100–150% RMT [ 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 ]. Bowtell et al [ 162 ] also found no change in resting MEPs following caffeine intake, while MEPs obtained during maximal contraction were potentiated by caffeine.…”
Section: Caffeinementioning
confidence: 99%
See 3 more Smart Citations